И.ЮСУПОВ ШЫҒАРМАЛАРЫНДА ФРАЗЕОЛОГИЯЛЫҚ СӨЗ ДИЗБЕКЛЕРИНИҢ ЖУМСАЛЫЎ ӨЗГЕШЕЛИГИ - Алламбергенова, Г.А.; Уснатдинова, А.К. (SCIENCE and SOCIETY, 2016)
The article deals with the pecularities of using phraseological words in the poetry of I.Yusupov and facilities of their image have been revealed.